2002
DOI: 10.1177/070674370204700609
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Intimidation in the Psychiatric Educational Environment in Edmonton, Alberta

Abstract: Reported perceptions and personal experiences of intimidation within the psychiatric learning environment in Edmonton are low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…The main form of this intimidation and harassment was in inappropriate verbal comments (66%). These results seem quite different from a previous study of psychiatry residents in Edmonton, Alberta, which concluded that intimidation in the psychiatric educational environment was not a significant issue [23]. However, due to the setup of our study we did not choose to stratify results from individual programs and therefore cannot directly comment on the psychiatry residents results.…”
Section: Discussioncontrasting
confidence: 81%
“…The main form of this intimidation and harassment was in inappropriate verbal comments (66%). These results seem quite different from a previous study of psychiatry residents in Edmonton, Alberta, which concluded that intimidation in the psychiatric educational environment was not a significant issue [23]. However, due to the setup of our study we did not choose to stratify results from individual programs and therefore cannot directly comment on the psychiatry residents results.…”
Section: Discussioncontrasting
confidence: 81%
“…Sizeable minorities of residents had reported being severely criticized or humiliated by an attending or had observed this happening to others [9] or had experienced bullying behaviors in the preceding year [33,34]. In the Canadian study, the perception of intimidating behaviors, including threats and the abuse of power, was generally low in the working environment [32].…”
Section: Mistreatment By Colleaguesmentioning
confidence: 88%
“…Information on mistreatment specific to psychiatric trainees is lacking, especially in American settings [31]. Four noteworthy studies of which we are aware, all of which are now dated, originate from Australia [9], Canada [32], UK [33], and Pakistan [34]. Sizeable minorities of residents had reported being severely criticized or humiliated by an attending or had observed this happening to others [9] or had experienced bullying behaviors in the preceding year [33,34].…”
Section: Mistreatment By Colleaguesmentioning
confidence: 99%
“…In seeking explanations, some students concluded that teachers use intimidation and humiliation because they do not have a reliable range of more effective teaching skills . Others concluded that these practices have become entrenched in the hierarchical culture of medicine over generations …”
Section: Discussionmentioning
confidence: 99%